Differences in physical fitness and throwing velocity among elite and amateur male handball players - Gorostiaga, E. M.; Granados, C.; Ibanez, J.; Izquierdo, M. (International Journal of Sports Medicine, 2005)
This study compared physical characteristics (body height, body mass [BM], body fat [BF], and free fatty mass [FFM]), one repetition maximum bench-press (1RMBP), jumping explosive strength (VJ), handball throwing velocity, power-load relationship of the leg and arm extensor muscles, 5- and 15-m sprint running time, and running endurance in two handball male teams: elite team, one of the world's leading teams (EM, n = 15) and amateur team, playing in the Spanish National Second Division (AM, n = 15). EM had similar values in body height, BF, VJ, 5- and 15-m sprint running time and running endurance than AM. However, the EM group gave higher values in BM (95.2 ± 13 kg vs. 82.4 ± 10 kg, p < 0.05), FFM (81.7 ± 9 kg vs. 72.4 ± 7 kg, p < 0.05), 1RMBP (107 ± 12 kg vs. 83 ± 10 kg, p < 0.001), muscle power during bench-press (18 - 21 %, p < 0.05) and half squat (13 - 17 %), and throwing velocities at standing (23.8 ± 1.9 m · s-1 vs. 21.8 ± 1.6 m · s-1, p < 0.05) and 3-step running (25.3 ± 2.2 m · s-1 vs. 22.9 ± 1.4 m · s-1, p < 0.05) actions than the AM group. Significant correlations (r = 0.67 - 0.71, p < 0.05 - 0.01) were observed in EM and AM between individual values of velocity at 30 % of 1RMBP and individual values of ball velocity during a standing throw. Significant correlations were observed in EM, but not in AM, between the individual values of velocity during 3-step running throw and the individual values of velocity at 30 % of 1RMBP (r = 0.72, p < 0.05), as well as the individual values of power at 100 % of body mass during half-squat actions (r = 0.62, p < 0.05). The present results suggest that more muscular and powerful players are at an advantage in handball. The differences observed in free fatty mass could partly explain the differences observed between groups in absolute maximal strength and muscle power. In EM, higher efficiency in handball throwing velocity may be associated with both upper and lower extremity power output capabilities, whereas in AM this relationship may be different. Endurance capacity does not seem to represent a limitation for elite performance in handball.